Cost-utility analysis of abatacept in rheumatoid arthritis in Italy - de Portu, Simona; Mantovani, Lorenzo Giovanni; Olivieri, Ignazio (Farmeconomia. Health economics and therapeutic pathways, 2008)
Objective: a substantial number of patients with rheumatoid arthritis (RA) have an insufficient or unsustained response to Tumor Necrosis Factor-α antagonists (anti-TNFs). The aim of the present study was to estimate the cost-utility of abatacept, a new selective T-cell co-stimulation modulator, in patients with moderately to severely active RA and an insufficient response or intolerance to anti-TNFs in the Italian setting. Methods: a probabilistic patient level simulation model was developed to estimate long-term costs and health outcomes of abatacept versus anti-TNFs (etanercept, adalimumab, infliximab) in RA patients. The model predicted patients’ HAQ (Health Assessment Questionnaire) scores over time based on the initial response to treatment (% change in HAQ score at six months). Responding patients continued treatment with a reduced rate of HAQ progression until long-term treatment failure. Health-state utilities and use of health care resources (excluding RA therapies) were assumed to depend on HAQ scores. The model used data from a Phase III clinical trial of abatacept in patients with inadequate response to anti-TNFs (Abatacept Trial in Treatment of anti-TNF Inadequate Responders [ATTAIN]) and various secondary data sources. The study was performed using the National Health Service (NHS) perspective. Cost-utility of abatacept vs other anti-TNFs was derived in terms of incremental cost per quality-adjusted life-year (QALY) gained based on a lifetime horizon with costs expressed in Euros. Single-way sensitivity analyses were performed on key parameters. Costs and health effects were discounted at 3% annually. Results: abatacept therapy was estimated to yield 1.18 additional QALYs per patient (5.02 abatacept vs 3.84 anti-TNFs) at an incremental cost of € 21,996.41 based on a 20 years time horizon. Cost per QALY gained was € 18,567.24. These results were robust to variation of key model parameters and are well within the usual cost-utility acceptance ranges. Conclusions: This study shows that in Italy, compared to anti-TNFs, abatacept therapy is cost-effective in patients with moderately to severely active RA and with an insufficient response or intolerance to anti-TNFs.